Will I see you at work? Ethnic workplace segregation in Sweden 1985 - 2002 - Olof Åslund; Oskar Nordström Skans (Institute for Labour Market Policy Evaluation (IFAU), 2005)
We study ethnic workplace segregation in Sweden using linked employer-employee data covering the entire working-age Swedish population during 1985–2002. Segregation is measured as overexposure to a particular group, taking into account the distribution of human capital, industry and geography. We find considerable workplace segregation between immigrants and natives but the results differ substantially between ethnic groups. Segregation has increased during the period, mainly due to changes in the ethnic composition. Immigrants are particularly overexposed to workers from their own birth region but also to other immigrants. Children to immigrants are only overexposed to immigrants from their parents region of birth. Segregation—particularly in the immigrant-native dimension—is in general negatively correlated with economic status.
Keywords: J15; J23; J42; J62; 330; Workplace segregation; ethnic minorities; immigrant assimilation; Ethnische Gruppe; Arbeitsplatz; Segregation; Schweden